What does the way crime was organised yesterday tell us about the way crime is organised today and will be tomorrow?. Issue 2 (5th May 2015) - Bill Tupman, Dr. Yuliya Zabyelina, Professor; Tupman, Bill
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to assess what an overview of theoretical literature and case study material can tell us about the different ways crime has been organised in the past in different cultures and whether this has any impact on the ways in which crime may be organised in the present and the future. Design/methodology/approach – The analysis is based on an examination of Mcintyre's work on how crime is organised and later political, economic and civil society views of criminality. Brief discussion of case studies involving the UK, The Netherlands, the Arab world, Ethiopia and Russia is used to see how crime was organised there in the past. Findings – There is a greater variety of variables in the way crime was organised historically than McIntyre suggests, and an examination of civil society might pay greater dividends than even looking at politics or economic aspects of organised crime. Research limitations/implications – The study is preliminary. More historical case study material needs to be accessed. Originality/value – There are many research case studies, particularly at PhD level and in subjects other than criminology, such as history, language studies and cultural studies generally, which have not been brought together to present an overall picture. This paper is a first step in that direction.